KAJIAN POTENSI KOLEKSI POHON LOKAL KEBUN RAYA CIBODAS UNTUK FUNGSI ESTETIKA DALAM LANSKAP - Muhammad Amin Shodiq; Tati Budiarti; Nizar Nasrullah (Jurnal Lanskap Indonesia, 2018)
Trees in the landscape have many important roles, one of them is aesthetics function. Therefore, tree species selection must be considered well. Indonesia has big number of tree biodiversity that can use for tree selection purposes. The selection can be considered based on physical characteristics and ecological characteristics of the tree species. Therefore, purposes of this study are 1) to identify ecological distribution of native tree species in Java island, 2) to identify native tree species which have high aesthetic value, and 3) to arrange native tree species list that have potential to be developed for aesthetic use in the landscape. This study conducted in  Cibodas Botanical Garden. The method used for this research is literature study from Botanical Garden Catalogue, direct survey method, aesthetic analyze using Key Performance Index for aesthetic quality assessment. The results of this research is there are 223  Java Island native tree species collection in Cibodas Botanical Garden.  The habitat of these collections of tree species is evenly distributed throughout the island of Java. Most can grow well in tropical zones (0-1000 masl) and tropical-mountain zones (0-2400 masl). Based on the aesthetic criteria assessment there are 50 species belonging to the good category, 101 species are included in the moderate category, and only one species is categorized as bad.